Predictors of hospital readmission two years after coronary artery bypass grafting. - Herlitz, J. (1997)
OBJECTIVE: To determine the clinical factors before, and in association with, coronary artery bypass grafting (CABG) that increase the risk of readmission to hospital in the first two years after surgery. PATIENTS: All patients in western Sweden who had CABG without simultaneous valve surgery between 1 June 1988 and 1 June 1991. METHODS: All patients who were readmitted to hospital were evaluated by postal inquiry and hospital records. RESULTS: A total of 2121 patients were operated on, of whom 2037 were discharged from hospital. Information regarding readmission was missing in four patients, leaving 2033 patients; 44% were readmitted to hospital. The most common reasons for readmission were angina pectoris and congestive heart failure. There were 12 independent significant predictors for readmission: clinical history (a previous history of either congestive heart failure or myocardial infarction, or CABG); acute operation; postoperative complications (time in intensive care unit greater than two days, neurological complications); clinical findings four to seven days after the operation (arrhythmia, systolic murmur equivalent to mitral regurgitation); medication four to seven days after the operation (antidiabetics, diuretics for heart failure, other antiarrhythmics (other than beta blockers, calcium antagonists, and digitalis), and lack of treatment with aspirin). CONCLUSION: 44% of patients were readmitted to hospital two years after CABG. The most common reasons for readmission were angina pectoris and congestive heart failure. Four clinical markers predicted readmission: clinical history; acute operation status; postoperative complications; and clinical findings and medication four to seven days after operation.